2008
DOI: 10.1016/s2005-2901(09)60004-2
|View full text |Cite
|
Sign up to set email alerts
|

Novel Anatomic Structures in the Brain and Spinal Cord of Rabbit That May Belong to the Bonghan System of Potential Acupuncture Meridians

Abstract: Novel threadlike structures of 20 to 40 microm in diameter were observed running afloat in the cerebrospinal fluid of the brain ventricles and the spinal central canal of a rabbit. We developed an effective in situ staining technique using hematoxylin to visualize the threadlike structure. The presence of the rod-shaped nuclei in the threadlike structure was confirmed by various nucleus specific staining dyes such as 4',6'-diamidino-2-phenylindole, propidium iodide and yoyo-1. The threadlike structure was surr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
5

Relationship

4
6

Authors

Journals

citations
Cited by 66 publications
(29 citation statements)
references
References 15 publications
0
29
0
Order By: Relevance
“…The presence of the PVS was observed on the surfaces of internal organs like the liver, stomach, large intestine and bladder [4] .This subset of the PVS is called the organsurface PVS (OS-PVS). Another major subset, which has been observed, is the PVS floating in the flow of blood [5] and lymph [6] or in the cerebrospinal fluid of the brain and the spinal cord [7] .…”
Section: Reviewmentioning
confidence: 99%
“…The presence of the PVS was observed on the surfaces of internal organs like the liver, stomach, large intestine and bladder [4] .This subset of the PVS is called the organsurface PVS (OS-PVS). Another major subset, which has been observed, is the PVS floating in the flow of blood [5] and lymph [6] or in the cerebrospinal fluid of the brain and the spinal cord [7] .…”
Section: Reviewmentioning
confidence: 99%
“…The major achievement of the group is the identification and observation of the PVS in various organs of different kinds of animals, and the advancement of technical methods for identifying the PVS. For example, the PVS was observed in the lymphatic vessels of rabbits [10, 11], in the brains and spinal cords of rabbits [12] and in the brains of rats [13]. Moreover, for the first time, the PVSs freely floating in bovine heart chambers were observed [14].…”
Section: What We Know About the Pvsmentioning
confidence: 99%
“…Nevertheless, recent intensive and systematic research on the primordial vascular system has revealed its presence throughout an animal’s body [4]. Since 2002, primordial vascular systems have been reported to exist in blood vessels [5,6,7], in lymph vessels [8,9,10], in brain ventricles and spinal cords [11], on internal organ surfaces [12,13,14,15] and a skin tumor fasciae [16]. Multiple channels in a primordial vessel were observed in morphological studies by using hematoxylin-eosin staining methods [17] and various types of electron microscopy [13].…”
Section: Introductionmentioning
confidence: 99%